Mapping of measured concentrations of persistent organic pollutants and polycyclic aromatic hydrocarbons in mosses and correlation of their surface estimations with maps on modelled atmospheric deposition in Central Europe - Schröder, Winfried; Nickel, Stefan; Dreyer, Annekatrin (Universität Vechta, 2025)
Background: The 2020 moss survey in Germany was designed as a pilot study and aimed to 1. validate the analysis of various organic contaminants developed in the previous moss survey; 2. develop the microplastic analysis methodology; 3. analyse the spatial distribution of persistent organic pollutants as well as polycyclic aromatic hydrocarbons in moss samples collected in Germany in 2020; and 4. compare the spatial deposition patterns with the results of current atmospheric deposition models. This article describes the latter objective Methods: The collection of mosses at 21 sites within Germany and the chemical analysis of organic pollutants was carried out according to ICP Vegetation (Heavy metals, nitrogen and POPs in European mosses. Monitoring manual survey 2020. Bangor (United Kingdom) and Dubna (Russian Federation), 2020). Geostatistical methods were used to analyse the spatial structure of the discrete measurement data and to produce maps based on this. The mapped concentrations in the mosses were compared with the modelled total annual deposition. Results: The spatial distribution of the substances often shows a concentration gradient with higher values in densely populated and industrialised areas in western Germany and lower concentrations in eastern areas. A triangle with comparatively higher values in central Germany is recognisable. No correlations were found between the concentration of benzo[a]pyrene (B[a]P) in the mosses and the modelled B[a]P deposition. However, the direct comparison at the moss sampling sites shows better agreement between the measured and modelled data in the northwestern half of Germany than in the other regions. Medium correlations were found between the concentrations of polychlorinated dibenzo-p-dioxins and furans (PCDD/F) in the mosses and the modelled PCDD/F deposition, and strong and very strong correlations were found with the geostatistical surface estimates. The most obvious similarities in the spatial patterns of the measured PCDD/F and modelled data were found in southern Bavaria, in a strip from North Rhine-Westphalia via northern Hesse to Thuringia and in the triangle between Mecklenburg-Western Pomerania, northern Brandenburg and eastern Lower Saxony. Conclusions: The study made it possible to describe the spatial distribution of persistent organic substances and polycyclic aromatic hydrocarbons in Germany and, at least in the case of PCDD/F, produced a good agreement between the modelled deposition and the measured concentrations in mosses. The moss data should be analysed in greater depth and statistically validated.
Diese Untersuchung wurde vom Umweltbundesamt gefördert [UBA FKz 3720632010]
Keywords: EMEP deposition modelling; ICP Vegetation moss survey; Kriging; Mapping; Surface estimation; Variogram analysis; Geschichte und Geografie::910 Geografie, Reisen